2009
DOI: 10.1042/bj20091500
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory factors controlling transcription of Saccharomyces cerevisiae IXR1 by oxygen levels: a model of transcriptional adaptation from aerobiosis to hypoxia implicating ROX1 and IXR1 cross-regulation

Abstract: Ixr1p from Saccharomyces cerevisiae has been previously studied because it binds to DNA containing intrastrand cross-links formed by the anticancer drug cisplatin. Ixr1p is also a transcriptional regulator of anaerobic/hypoxic genes, such as SRP1/TIR1, which encodes a stress-response cell wall manoprotein, and COX5B, which encodes the Vb subunit of the mitochondrial complex cytochrome c oxidase. However, factors controlling IXR1 expression remained unexplored. In the present study we show that IXR1 mRNA levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 46 publications
3
27
0
Order By: Relevance
“…The Northern blot analyses presented in Figure 1C showed that the expression of ROX1 and ORD1 in the yeast genetic background used here (W303) is not cross-regulated as previously proposed for BY4741 cells (13). This was further substantiated by quantitative polymerase chain reaction (PCR) analyses that showed that expression of ROX1 and ORD1 both in normoxia and in anoxia is independent of their respective protein products ( Supplementary Fig.…”
Section: Rox1 and Ord1 Play Complementary But Nonoverlapping Roles Onsupporting
confidence: 52%
“…The Northern blot analyses presented in Figure 1C showed that the expression of ROX1 and ORD1 in the yeast genetic background used here (W303) is not cross-regulated as previously proposed for BY4741 cells (13). This was further substantiated by quantitative polymerase chain reaction (PCR) analyses that showed that expression of ROX1 and ORD1 both in normoxia and in anoxia is independent of their respective protein products ( Supplementary Fig.…”
Section: Rox1 and Ord1 Play Complementary But Nonoverlapping Roles Onsupporting
confidence: 52%
“…Besides, the effect of ∆ixr1 is epistatic to ∆yap1 (Bourdineaud et al, 2000). IXR1 expression is moderately activated by H 2 O 2 and this induction is Yap1-dependent (Castro-Prego et al, 2010a). In multi-cellular eukaryotes connexions between the oxidative stress response and IXR1 homologues also exist.…”
Section: The Relationships Between Ixr1 Rox1 and The Oxidative Stresmentioning
confidence: 93%
“…Structurally, both contain HMG (high-mobility group) domains, which bind to and bend DNA (Deckert et al, 1995;Deckert et al, 1999;. Functionally, both control genes that are expressed at higher levels when oxygen is low (hypoxia) or absent (anoxia) than during normoxia (Bourdineaud et al, 2000;Castro-Prego et al, 2010a, 2010bKastaniotis & Zitomer, 2000;Klinkenberg et al, 2005;Lambert et al, 1994;Zitomer & Lowry, 1992;Zitomer et al, 1997;). Moreover, a transcriptional cross-regulation between the genes ROX1 and IXR1 has been reported (Castro-Prego et al, 2010b).…”
Section: The Relationships Between Ixr1 Rox1 and The Oxidative Stresmentioning
confidence: 99%
See 1 more Smart Citation
“…Rox1p and Mot3p repress the aerobic expression of HEM13 (Klinkenberg et al 2005), while Ixr1p is a positive regulator of HEM13 transcription in hypoxia (CastroPrego et al 2010a). Besides, a transcriptional cross-regulation between the genes ROX1 and IXR1 exists (Castro-Prego et al 2010b). In aerobiosis, low levels of IXR1 expression are maintained by Rox1p repression through the general co-repressor complex Tup1-Ssn6.…”
Section: Introductionmentioning
confidence: 99%